AB0096 Expression and function of neuropeptide y receptors in human articular cartilage: influence of gender and osteoarthritis. (12th June 2018) - Ferreira, I.; Sousa, C.; Silva, S.; Judas, F.; Cavadas, C.; Mendes, A.F.
Abstract : Background: Elevated levels of neuropeptide Y (NPY) were reported in osteoarthritic (OA) joints 1 . No information exists regarding the role of NPY in OA joints, besides mediating or potentiating nociceptive transmission. Objectives: To determine whether NPY receptors are present and functional in human chondrocytes, by evaluating the ability of NPY to activate important signalling pathways and to modulate autophagy, which was shown to be induced by this neuropeptide in hypothalamic neurons 2 and to be a crucial homeostatic mechanism in chondrocytes, whose reduction contributes to OA pathogenesis 3 . Methods: Immunofluorescence for the NPY receptor subtypes, Y1, Y2 and Y5, was performed in the human chondrocytic cell line, C28/I2, and in human cartilage sections obtained from multi-organ donors (4 males, 55–75 years old, mean=67.25, 3 females, 33–68 years old, mean=55.33) at the Bone and Tissue Bank, University and Hospital Centre of Coimbra, with approval by the Ethics Committee. Phosphorylated levels of JNK, p38, ERK1/2, PKA, Akt and PKC and the levels of LC3B-I and II were evaluated by Western Blot of total cell extracts from C28/I2 cells. Results: Immunoreactivity for Y1, Y2 and Y5 NPY receptors was observed in C28/I2 cells. In human cartilage, a positive signal was found for the Y2 receptor in all samples while Y5 receptor immunoreactivity was undetectable, regardless of disease state, gender and age of the donors. Y1 receptor immunoreactivity was observed in male and female OA cartilage samples, as well as in those from non-OA females, but not in those from non-OA males. 50 nM NPY was sufficient to significantly increase the levels of phospho-JNK, -p38, -ERK1/2, -PKA, Akt and PKC with similar kinetics, but much slower than IL-1β. A 6 hour stimulation with 50 or 100 nM NPY decreased LC3B-I and II levels in comparison with untreated cells. In the presence of chloroquine (ChQ), NPY increased LC3B-II levels relative to those found in cells treated with ChQ alone, indicating an increased delivery of LC3B-II to the lysosome consistent with autophagy activation by NPY. Conclusions: This study shows that distinct NPY receptor subtypes are present and functional in C28/I2 cells and in human chondrocytes in situ in the articular cartilage, strongly suggesting that non-neuronal cells and tissues of the joints, namely chondrocytes, are relevant as NPY targets. The presence of each receptor subtype seems to be determined by gender and, in males, also by the disease state. The role of age is unclear as most cartilage donors were aged >55 years old. Future studies will be addressed at further elucidating the role of NPY and its receptors in modulating male and female chondrocyte functions, both in health, ageing and osteoarthritis. References: [1] Wang, et al. BMC Musculoskelet Disord2014;15:319. [2] Aveleira, et al. PNAS2015;112:E1642-E1651. [3] Ribeiro, et al. Osteoarthritis Cartilage2016;24:2116–2125. Acknowledgements: This work was funded by European Regional Development Fund (FEDER) through the Operational Programme Competitiveness Factors – COMPETE: HealthyAging 2020 (CENTRO-01–0145-FEDER-000012), and by National Funds through FCT-Foundation for Science and Technology under the Strategic Project UID/NEU/04539/2013 and the project PTDC/EMS-TEC/3263/2014. Disclosure of Interest: None declared